Knockdown of SNHG14 Alleviates MPP+-Induced Injury in the Cell Model of Parkinson’s Disease by Targeting the miR-214-3p/KLF4 Axis - Zhou, Shufang; Zhang, Dan; Guo, Junnan; Zhang, Junshi; Chen, Yong (Frontiers in Neuroscience, 2020)
Background: Parkinson’s disease (PD) is the second most prevalent neurodegenerative disease. Long noncoding RNA (lncRNA) small nucleolar RNA host gene 14 (SNHG14) has been demonstrated as an essential regulator in PD pathology. However, the functional mechanisms that it plays in PD remain largely elusive. Methods: We used 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and 1-methyl-4-phenylpyridinium (MPP+) to establish PD mouse and cell models. The levels of SNHG14, miR-214-3p and Krüppel-like factor 4 (KLF4) were gauged by quantitative real-time polymerase chain reaction (qRT-PCR) or western blot analysis. Cell viability and apoptosis were determined using the Cell Counting-8 Kit (CCK-8) assay and flow cytometry, respectively. The levels of inflammatory cytokines were evaluated by enzyme-linked immunosorbent assay (ELISA). The interplays among SNHG14, miR-214-3p and KLF4 were confirmed by dual-luciferase reporter and RNA immunoprecipitation (RIP) assays. Results: Our data indicated that SNHG14 was up-regulated and miR-214-3p was down-regulated in PD models. SNHG14 knockdown ameliorated MPP+-stimulated damage in SK-N-SH cells, as presented by the enhancement in cell viability and the suppression in cell apoptosis and inflammation. Mechanistically, SNHG14 sequestered miR-214-3p via binding to miR-214-3p, and SNHG14 knockdown protected SK-N-SH cell from MPP+-stimulated cytotoxicity by miR-214-3p. KLF4 was a direct target of miR-214-3p, and SNHG14 regulated KLF4 expression by acting as a miR-214-3p sponge. Furthermore, miR-214-3p overexpression alleviated MPP+-stimulated damage in SK-N-SH cells by down-regulating KLF4. Conclusion: Our current study first demonstrated the protective effect of SNHG14 knockdown on MPP+-stimulated cytotoxicity in SK-N-SH cells at least partly via targeting the miR-214-3p/KLF4 axis, illuminating a promising target for PD intervention and treatment.